Challenges and Solutions for Law Enforcement in Handling Online Pornography and Prostitution Crimes - Hidayat, Sarip (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The development of digital technology has pushed the emergence of various forms of cybercrime, including criminal acts of pornography and online prostitution which are increasingly rampant in Indonesia. This crime not only impacts the morality of society, but also gives rise to serious challenges in the process of law enforcement.Purposes of the Research: This research aims to identify various challenges faced by law enforcement apparatus in uncovering and handling criminal acts mentioned, as well as offering strategic solutions that can be applied.Methods of the Research: The method used in this study is a normative legal approach with analysis to regulatory legislation, literature studies, and actual cases.Results Main Findings of the Research: Research results show that challenges main covering weakness regulation, limited source Power humans and technology, anonymity of actors in the digital world, as well as lack of Work The same international. To overcome the problem said, legal reform is needed, increasing capacity of law enforcers, utilization of digital forensic technology, as well as a collaborative inter-agency and participation society approach. With a comprehensive and adaptive strategy, it is hoped that law enforcement against criminal acts of online pornography and prostitution can be more effective and sustainable.